Chromium in soil organic matter and cowpea after four consecutive annual applications of composted tannery sludge - Jacinto Oliveira, Mara Lucia; Ferreira de Araujo, Ademir Sergio; Melo, Wanderley Jose de [UNESP] (Soc Brasileira De Ciencia Do Solo, 2015)
Tannery sludge contains high concentrations of inorganic elements, such as chromium (Cr), which may lead to environmental pollution and affect human health The behavior of Cr in organic matter fractions and in the growth of cowpea (Vigna unguiculata L.) was studied in a sandy soil after four consecutive annual applications of composted tannery sludge (CTS). Over a four-year period, CTS was applied on permanent plots (2 x 5 m) and incorporated in the soil (0-20 cm) at the rates of 0, 2.5, 5.0, 10.0, and 20.0 Mg ha(-1) (dry weight basis). These treatments were replicated four times in a randomized block design. In the fourth year, cowpea was planted and grown for 50 days, at which time we analyzed the Cr concentrations in the soil, in the fulvic acid, humic acid, and humin fractions, and in the leaves, pods, and grains of cowpea. Composted tannery sludge led to an increase in Cr concentration in the soil. Among the humic substances, the highest Cr concentration was found in humin. The application rates of CTS significantly increased Cr concentration in leaves and grains.

O lodo de curtume compostado contém elevadas concentrações de elementos inorgânicos, como o crômio (Cr), que podem levar à poluição ambiental e influenciar na saúde humana. O comportamento envolvendo o Cr nas frações da matéria orgânica e no crescimento do feijão-caupi (Vigna unguiculata L.) foi estudado em solo arenoso, após quatro anos de aplicações anuais consecutivas de lodo de curtume compostado (LCC). Durante quatro anos, o LCC foi aplicado em parcelas permanentes (2 × 5 m) e incorporado no solo (0-20 cm), nas doses de 0; 2,5; 5,0; 10,0 e 20,0 Mg ha-1 (base seca). Esses tratamentos foram repetidos quatro vezes em blocos ao acaso. No quarto ano, o feijão-caupi foi semeado e cresceu por 50 dias, quando se analisaram as concentrações de Cr no solo, nas frações ácidos fúlvicos, ácidos húmicos e humina, nas folhas, nas vagens e nos grãos do feijão-caupi. O LCC promoveu aumento na concentração de Cr no solo. Entre as substâncias húmicas, a maior concentração de Cr foi encontrada na humina. As doses de LCC elevaram o teor de Cr nas folhas e grãos.
Cromio na matéria orgânica do solo e feijão-caupi, após quatro aplicações anuais consecutivas de lodo de curtume compostado
Keywords: Soil contamination; Humic substances; Solid residue; Heavy metals; Plant growth; Trace elements